PRAEDICATIO EST: HUMBERT OF ROMANS, JACOBUS OF FUSIGNANO AND GIORDANO DA PISA ON THE PREACHING OF THE ORDER OF THE FRIAR PREACHERS IN THE LATE XIIITH AND EARLY XIVTH CENTURY - Alves, Aléssio Alonso (Revista de Historia Social y de las Mentalidades, 2020)
The purpose of this article is to establish a synthetic concept of preaching according with the statements expressed by three Friars Preachers in the second half of the thirteenth and early fourteenth century. Starting with the definition by the theologian Alain de Lille (1128-1202), today taken as paradigmatic, three works of different natures are analysed and compared: De eruditione religiosorum praedicatorum (1263), by Humbert of Romans (1190-1277); the Libellus artis predicatorie (1290), by Jacobus of Fusignano (? -1333); and the reportationes of two sermons (1304) by Giordano da Pisa (c. 1260-1311). As conclusion, preaching is synthesized into a concept as an instruction on the Holy Scriptures, divine things, faith and truth; as well as about morals, vices and sins, whose goal is the salvation of its audience.
Keywords: Preaching; Friars Preachers; Dominican Order; Sermon